EVALUATION OF RICE FOR POOR SOCIETY PROGRAMIN WONOKUSUMO VILLAGE SEMAMPIR SUBDISTRICT - RIZKA NUR ALFIANTI (Universitas Negeri Surabaya, 2013)
EVALUATION OF RICE FOR POOR SOCIETY PROGRAMIN WONOKUSUMO VILLAGE SEMAMPIR SUBDISTRICTSURABAYA CITYRizka Nur AlfiantiDosen Pembimbing: Tauran, S.Sos.,M.Soc,ScABSTRACTRice for poor society program is part of the poverty prevention program to meet the needs of a family-based staple food for the poor society. Wonokusumo is one of village that implementing it by the number of poor households of 3,209 heads of household. The purpose of evaluation it to assess how far the program has achieved its goal successfully and targets of government programs. Its goal is to reduce the target household’s expanding burden by fulfillment its staple food in rice. The aim this paper is to evaluate rice for poor society program in Wonokusumo Village Semampir Subdistrict Surabaya City by six indicators (six right) include Target, Right Quantity, Right Price, Right Time, Right Administration and Right Quality.The method is descriptive research with quantitative approach. Research location is in Wonokusumo Village Semampir Subdistrict Surabaya City. Data collection techniques have conducted by distributing questionnaires, interview and observation. Sampling technique use incidental sampling with Slovin formula. The research indicators are Target, Right Quantity, Right Price, Right Time,Right Administration and right Quality. Data analyze was descriptive quantitatively by percentage and qualitative data analyze of interview.The result shows that rice for poor society program in Wonokusumo Village Semampir Subdistrict Surabaya City does not has six right indicators. There are unexact poor households target. The quantity that received by poor household is not 15 kilograms but 3 kilograms until 7,5 kilograms. The price is not 1.600 IDR per kilogram but 2.000 IDR per kilogram. Based on time, it is not distributed twelve times in a year. Taking rice not use the rice for poor society but by coupons created by local RT or RW. The rice quality is improper to consumed. Suggestion of this study that the government is more disciplined to this program to predefined rules.Keywords: Evalution, Rice for Poor Society Program, Poor Household